Efficient deprotection of dithioacetals to carbonyls using Oxone-KBr in aqueous acetonitrile - Desai, Uday V.; Pore, D. M.; Tamhankar, B. V.; Jadhav, Sushilkumar A.; Wadgaonkar, P. P. (Tetrahedron Letters, 2006)
A simple and efficient method has been developed for the chemoselective dethioacetalization of dithioacetals to aldehydes and ketones using Oxone-KBr in aqueous acetonitrile at room temperature. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: deprotection; dethioacetalization; Oxone

Synthesis and characterization of cholesteric thermotropic liquid crystalline polyesters - Jadhav, Sushilkumar A.; Chougule, Rahul R.; Shinde, Yogesh A.; Chavan, Nayaku (Journal of Applied Polymer Science, 2006)
Cholesteric liquid crystalline polyesters were successfully synthesized from isosorbide, methyl hydroquinone, and isophthaloyl chloride. Homo/copolyesters were synthesized by the solution polycondensation method, for which a mild organic base such as pyridine was employed. Inherent viscosities of polyesters P-3-P-5 were in the range of 0.31-0.39 dL/g at 25 degrees C in chloroform, and polyesters P-1 and P-2 were insoluble in chloroform. Homo/copolyesters based on isosorbide, methyl hydroquinone, and isophthalic acid had thermal stability at more than 300 degrees C on the basis of 10% weight loss. The thermotropic liquid crystalline properties were examined by differential scanning calorimetry and polarizing optical microscopy. Wide-angle X-ray diffraction study demonstrated that polyesters P-1, P-2, and P-3 were semicrystalline, whereas the degree of crystallinity of polyesters P-4 and P-5 was less than 5%. Copolyester P-4 showed formation of a yellow iridescent streak at 209 degrees C on heating and development of a Grand-jean texture at 270 degrees C on heating. These are typical textures of the cholesteric liquid crystalline phase. (c) 2006 Wiley Periodicals, Inc.
Keywords: cholesteric liquid crystalline polymers (ChLCP); Differential scanning calorimetry (DSC); optical microscopy; solution polycondensation; Thermogravimetric analysis (TGA); viscosity

Aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups: synthesis and characterization - Bapat, Snehalata P.; Jadhav, Sushilkumar A.; Valsange, Nitin G.; Tawade, Bhausaheb V.; Honkhambe, Pandurang N.; Chavan, Nayaku N.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2017)
A new bisphenol, 1,1-bis-[(4-hydroxyphenyl)-1-(4-phenylsulfonyl) phenyl)] ethane (DPSBP) was synthesized starting from diphenylsulfide and was characterized by spectroscopic methods. DPSBP was polycondensed with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of IPC and TPC (50: 50 mol%) by phase-transfer catalysed interfacial polymerization method to obtain aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups. A series of copolyesters was also obtained by polycondensation of varying molar proportions of DPSBP and bisphenol-A (BPA) with TPC. (Co) polyesters exhibited inherent viscosities in the range 0.56-1.57 dLg(-1) and number average molecular weights (Mn) were in the range 28,650-80,230 g/mol. Polyesters dissolved readily in common organic solvents such as dichloromethane, chloroform, tetrahydrofuran and aprotic polar solvents such as N-methylpyrrolidone, and N, N-dimethylacetamide. Tough, transparent and flexible films of polyesters could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of aromatic polyesters. Polyesters showed T-g values in the range 223-257 degrees C while T-10 values were in the range of 469-484 degrees C indicating their excellent thermal stability.
Keywords: Aromatic polyesters; Bulky pendent group; solubility; thermal stability